2015
DOI: 10.1016/j.lungcan.2015.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine induces resistance to erlotinib via cross-talk between α 1 nAChR and EGFR in the non-small cell lung cancer xenograft model

Abstract: These results suggest that nicotine contributes to the progression and erlotinib-resistance of the NSCLC xenograft model via the cooperation between nAChR and EGFR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 38 publications
4
29
0
Order By: Relevance
“…However, a few studies have demonstrated the effect of nicotine on anti-EGFR cancer therapy. In non-small cell lung cancer, nicotine induces resistance to erlotinib and gefitinib, which are EGFR tyrosine kinase inhibitors (23,46). In colorectal cancer, cigarette smoking during anticancer treatment with a cetuximab-based regimen reduces the therapeutic benefit (47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a few studies have demonstrated the effect of nicotine on anti-EGFR cancer therapy. In non-small cell lung cancer, nicotine induces resistance to erlotinib and gefitinib, which are EGFR tyrosine kinase inhibitors (23,46). In colorectal cancer, cigarette smoking during anticancer treatment with a cetuximab-based regimen reduces the therapeutic benefit (47).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, nicotine decreases the expression of EGFR, and enhances the accumulation of p-EGFR in the nucleus, thereby increasing proliferation of breast cancer cells (22). Finally, in lung cancer cells, nicotine serves a role in the resistance against EGFR inhibitors (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, nAChRs may be a promising molecular target to arrest lung cancer progression and reopen mitochondrial apoptotic pathways. Nicotine can induce erlotinib resistance via the crosstalk between α1nAChR and EGFR/AKT/ ERK signaling pathways in NSCLC [117]. A recent study suggested that smoking containing nicotine causes resistance to erlotinib therapy in NSCLC [118].…”
Section: The Potential Mechanisms Of Nicotine and Sirtuins On Drug Rementioning
confidence: 99%
“…nAChR signaling in mitochondria is stimulated and engages PI3K/AKT kinases, similar to those activated by plasma membrane nAChRs. Nicotine contributes to progression and erlotinib resistance in an NSCLC xenograft model through the nAChR-EGFR cooperation [117]. The nicotine-mediated α5nAChR/ AKT signaling pathway prevents cisplatin-induced cancer cell apoptosis [112].…”
Section: Sirt2-sirt7mentioning
confidence: 99%
“…Surprisingly, to our knowledge, only one study has been published involving systemic coadministration of nicotine and cancer chemotherapy in vivo. Li et al (2015) observed significant increases in PC9 human lung adenocarcinoma tumor volume in BALB/c nude mice following administration of erlotinib (100 mg/kg, by mouth) for 10 days in combination with 100 mg/ml nicotine in the drinking water or given i.v. (0.6 mg/kg, 5Â/week) when compared with erlotinib alone.…”
Section: Studies In Tumor-bearing Animalsmentioning
confidence: 99%